2020
DOI: 10.1007/s10071-020-01410-2
|View full text |Cite
|
Sign up to set email alerts
|

Who turns to the human? Companion pigs’ and dogs’ behaviour in the unsolvable task paradigm

Abstract: When facing an unsolvable problem, dogs exhibit spontaneous human-oriented behaviours (e.g. looking at the human partner, gaze alternations between the human and the target) sooner and for longer than domestic cats and hand-raised wolves. These behaviours have been interpreted as interspecific communicative acts aimed to initiate interaction. Here, we compare the emergence of human-oriented behaviours (e.g. orientation towards humans, orientation alternations, vocalizations) in similarly raised family dogs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…We carried out this study in a test room (4.45 m × 3.68 m room) of the Department of Ethology (Eötvös Loránd University, Hungary) in the presence of the animals' owners. No signs of excessive distress or fear, were shown by any of the subjects during this study, similar as in our previous work 35,36 .…”
Section: Subjectssupporting
confidence: 92%
“…We carried out this study in a test room (4.45 m × 3.68 m room) of the Department of Ethology (Eötvös Loránd University, Hungary) in the presence of the animals' owners. No signs of excessive distress or fear, were shown by any of the subjects during this study, similar as in our previous work 35,36 .…”
Section: Subjectssupporting
confidence: 92%
“…Thirdly, gaze alternations are considered as an indicator that human-directed gazing is referential (Gaunet 2010 ; Gaunet and Deputte 2011 ; Marshall-Pescini et al 2013 ; Miklósi et al 2000 ; Pérez Fraga et al 2021 ; Smith and Litchfield 2013 ). In the current study, as in previous studies, dogs performed gaze alternations, and the direction of gaze alternations was affected by the responsibility of the two persons present.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, variations of the ‘unsolvable task’ paradigm have been used in numerous studies to assess dogs’ cognitive abilities and to tease apart phylogenetic and ontogenetic effects on human-directed gazing in dogs, other canids (reviewed in Cavalli et al 2018 ; Mendes et al 2021 ), as well as other species (Alterisio et al 2018 ; Langbein et al 2018 ; Miklósi et al 2005 ; Pérez Fraga et al 2021 ; Zhang et al 2021 ). Several studies demonstrated that wolves show less ‘looking back’ than dogs do (Gácsi et al 2005 ; Marshall-Pescini et al 2017 ; Miklósi et al 2003 ; Udell 2015 ), while dingoes were found to show intermediate levels of human-directed gazing (Ballard et al 2021 ; Johnston et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, a comparison of the results of dogs and cats when two to three times as many cats are required for the same number of successfully tested subjects cannot be considered as a valid analysis at the group level. From a broader perspective, considering the growing number of comparative studies [ 54 ] where the validity of the species comparison can be compromised by either different or exactly the same test procedures, to figure out to what extent lab tests are feasible for a species is of crucial importance. Our findings have major implications in collecting reliable and repeatable data on cat behaviours and in ensuring optimal welfare, relevant not only in laboratory, but also in other settings (e.g., vet clinics).…”
Section: Discussionmentioning
confidence: 99%